The Effect of Dosage and Storage Time on the Formation of Bound Residues in Paddy, Milled Rice and Maize - Syed, Mohd Arif; Arshad, Juzu Hayati; Ramli, Johari; Muse, Radzali; Mahmood, Zabedah (Universiti Putra Malaysia Press, 1994)
Stored unmilled rice (paddy), milled rice and maize treated with radiolabelled malathion formed bound 14C residues. After 3 months of storage, the bound residues in the grains treated with 10J.Lg/g malathion accounted for 10.8, 6.5 and 13.3% of the applied dose in paddy, rice and maize respectively. After 6 months, the corresponding values of bound residues were 14.2, 4 and 17.7% respectively. Increasing the dosage of malathion to 50J.lg/ g does not significantly increase the percentage of the bound residues formed. However, the absolute amount increased by more than 410ld in all the grains tested.